Analysis Performance and Investment Simulation of Gas Fueling Station inside Gasoline Station without Pipeline Gas Distribution. Case Study Gasoline Station 34-40321. - Nurizki, Arif
Government of Indonesia has started an issue about fuel conversion from liquid fuel to gas although Gas Filing Station (GFS) in Indonesia is still rare. At a moment, gas distribution from motherstation to GFS is still using underground piping. For fulfill demands on the market, GFS will be built inside Gasoline Station’s area where its location is far from motherstation so that design must be modified to accommodate truck’s gas distribution in order to be sold much larger in volume. Overall plan contains design of Piping and Instrumentation Diagram (P&ID), systems performance calculation with total time as an output, and investment simulation. P&ID is designed by all demands from GFS and also valve’s selection based on its function. GFS’ system is designed to be a Fast Fill because of its limited area. Modifying system purposes to increase amount of gas volume because distribution is limited by a number of truck. Based on P&ID’s design, performance can be calculated by using Weymouth Equation with assumption: non ideal gas, adiabatic, non isentropic. In a cyclic of system will use 69 minutes to process the gas to be ready to be sold with most of its time used by compressor. Installation of SPBG needs an initial investment and as it runs and operates, it will earn some money in annual and reaches its break even point. Investment will be simulated in simple investment as two models with fee as independent variable from Rp 100,00 to Rp 500,00 each gas liter at 250 bar. From the investment model, Model A with fee Rp 400,00 each gas liter at 250 bar is the feasible one to be chosen because its IRR value is bigger than 30% with truck delivers 54 times in a month.